Analisis Dampak Export Restriction Komoditi Pertanian Terhadap Indonesia - Dian Verawati Panjaitan; Steven Raja Ingot; Arie Mardiansyah; Leo M. Christoffel (Jurnal Agribisnis Indonesia, 2020)
The discussion on Restrictions on Agricultural Exports (ER) in the World Trade Organization (WTO), which is a mechanism to temporarily stop the export of agricultural products aimed at preventing food shortages in exporting countries has been intensively negotiated. However, as a net importer of agricultural products and a member of the G33 countries, Indonesia must overcome the ER policy because it might have the potential to increase prices and threaten food security in the Indonesian domestic market. This study uses descriptive qualitative statistical analysis to determine the Import Dependency Ratio (IDR) and Independence Ratio (SSR) for five of Indonesia's main import agricultural products such as rice, corn, soybeans, wheat, and horticulture. Computable General Equilibrium (CGE) analysis using GTAP ver.9 is also used to analyze the impact of restrictions on exports of agricultural products for the five products analyzed on macroeconomic and sectoral indicators. Based on IDR and SSR it can be concluded that almost all G33 countries are highly dependent on wheat imports, as many as 36 countries are dependent on imported wheat with IDR values ​​varying between 70% - 215%. The analysis shows that export restrictions will harm Indonesia's macroeconomic. However, by sector, Indonesian farmers and producers can take advantage of the impact of the export restriction policy as an opportunity to increase their production in the context of meeting domestic demand as a result of declining demand for imported food products in the country.